Support Vector Machine Analysis of Functional Magnetic Resonance Imaging of Interoception Does Not Reliably Predict Individual Outcomes of Cognitive Behavioral Therapy in Panic Disorder with Agoraphobia - Sundermann, Benedikt; Bode, Jens; Lueken, Ulrike; Westphal, Dorte; Gerlach, Alexander L.; Straube, Benjamin; Wittchen, Hans-Ulrich; Ströhle, Andreas; Wittmann, André; Konrad, Carsten; Kircher, Tilo; Arolt, Volker; et al. (Frontiers in Psychiatry, 2017)
Background: The approach to apply multivariate pattern analyses (MVPA) based on neuroimaging data for outcome prediction holds out the prospect to improve therapeutic decisions in mental disorders. Patients suffering from panic disorder with agoraphobia (PD/AG) often exhibit an increased perception of bodily sensations. The purpose of this investigation was to assess whether multivariate classification applied to an fMRI interoception paradigm can predict individual responses to cognitive behavioral therapy (CBT) in PD/AG. Methods: This analysis is based on pretreatment fMRI data during an interoceptive challenge from a multi-center trial of the German PANIC-NET. Patients with DSM-IV PD/AG were dichotomized as responders (n = 30) or non-responders (n = 29) based on the primary outcome (Hamilton Anxiety scale reduction ≥ 50%) after 6 weeks of CBT (2 h/week). fMRI parametric maps were used as features for response classification with linear support vector machines (SVM) with or without automated feature selection. Predictive accuracies were assessed using cross validation and permutation testing. The influence of methodological parameters and the predictive ability for specific interoception-related symptom-reduction were further evaluated. Results: SVM did not reach sufficient overall predictive accuracies (38.0 to 54.2%) for anxiety reduction in the primary outcome. In the exploratory analyses better accuracies (66.7%) were achieved for predicting interoception-specific symptom relief as an alternative outcome domain. Subtle information regarding this alternative response criterion but not the primary outcome was revealed by post-hoc univariate comparisons. Conclusions: In contrast to reports on other neurofunctional probes, SVM based on an interoception paradigm was not able to reliably predict individual response to CBT. Results speak against the clinical applicability of this technique.